The Impact Of Implementing Infection Control Standards In Healthcare Facilities (The Review of Diabetic Studies, 2025)
Healthcare-associated infections (HAIs) pose a consistent international risk to patient safety and system effectiveness. Though there is a sound basis of evidence-based infection prevention and control (IPC) standards, there is a considerable lack of knowledge about the overall and causal influence of structured implementation of IPC programs on human, resource, and clinical outcomes in the Saudi Arabian healthcare setting. This research set out to measure the impacts of an IPC standards intervention in a tertiary care environment. The quasi-experimental, pretest-posttest design was used in two six-month periods. The intervention consisted of the introduction of a multimodal IPC bundle. They were evaluated through prospective HAI surveillance (CDC/NHSN definitions), paired survey of healthcare workers (HCWs) with validated instruments, and retrospective pharmacy/administrative data analysis. Statistical tests were performed on incidence rate ratios, paired t-tests, and multivariate logistic regression. HAI incidence density decreased by 33.4% (IRR: 0.67, 95% CI: 0.490.91, p=0.009) with a central line-associated bloodstream infection and catheter-associated urinary tract infection decreasing by 46.1 and 40.8 percent, respectively. The HCW knowledge scores improved by 14.3 percentage points (95% CI: 11.6 to 17.0, p